Effects of ionizing radiation on chondrocytes growth: work in progress - Mat Nawi, Nur Farhana; Sha'ban, Munirah; Zainuddin, Zainul Ibrahim (2016)
Purpose: To evaluate the possible effects of ionizing radiation on cellular morphology and growth kinetics of monolayer cultured chondrocytes.